Folded double layer: a novel nonlinear ion acoustic wave propagating obliquely in a magnetized plasma - Kamalam, T.; Ghosh, S. S. (My University, 2020)
A novel nonlinear structure is reported with a ‘near-unipolar’ solution which is obtained analytically by using Sagdeev pseudopotential technique for a three component magnetized plasma. The plasma is consisting of warm fluid ions and two types of electrons having Maxwell Boltzmann distributions. The structure is an amalgamation of the newly discovered super solitary wave and a conventional double layer. Because of the extra ‘wiggle’ or ‘fold’ in the usual monopolar electric field, it is named as ‘Folded Double Layer’. The presence of the extra wiggle, or ‘fold’, in the otherwise monopolar pulse may well modify the particle acceleration processes which remains hitherto unknown, or unnoticed, during the satellite observations.
Keywords: Nonlinear waves; Double layers; Magnetized plasmas